The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/pharmaceutics14030501
|View full text |Cite
|
Sign up to set email alerts
|

The Association between ABCG2 421C>A (rs2231142) Polymorphism and Rosuvastatin Pharmacokinetics: A Systematic Review and Meta-Analysis

Abstract: Although several studies have revealed the association between rosuvastatin pharmacokinetics and the ABCG2 421C>A (rs2231142) polymorphism, most studies were conducted with small sample sizes, making it challenging to apply the findings clinically. Therefore, the purpose of this study is to perform a meta-analysis of the relationship between the ABCG2 421C>A polymorphism and rosuvastatin pharmacokinetics. We searched three electronic databases, EMBASE, PubMed, and Web of Science, using search terms relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…ABCG2 is also a transporter protein, and its genetic variation ( ABCG2∗A , rs2231142, c.421C>A) is associated with higher plasma levels of rosuvastatin (Fig. 3) [31]. CPIC guidelines recommend prescribing lower rosuvastatin doses (<20 mg) in patients with poor ABCG2 function and if higher doses are needed, it's recommended to consider combination or alternative therapy [29 ▪ ].…”
Section: Pharmacogenetics To Guide Cardiovascular Drug Therapymentioning
confidence: 99%
“…ABCG2 is also a transporter protein, and its genetic variation ( ABCG2∗A , rs2231142, c.421C>A) is associated with higher plasma levels of rosuvastatin (Fig. 3) [31]. CPIC guidelines recommend prescribing lower rosuvastatin doses (<20 mg) in patients with poor ABCG2 function and if higher doses are needed, it's recommended to consider combination or alternative therapy [29 ▪ ].…”
Section: Pharmacogenetics To Guide Cardiovascular Drug Therapymentioning
confidence: 99%
“…Un metaanálisis que incluyó 423 pacientes demostró que los portadores del alelo A en ABCG2 421C>A tenían una concentración aumentada de rosuvastatina. Debido a que la frecuencia del alelo A en población asiática es elevada (0.29) la FDA recomienda reducir la dosis en estos pacientes [ 46 ].…”
Section: Farmacogenéticaunclassified
“…En la Tabla 4 se describen las recomendaciones terapéuticas sobre el ajuste de dosis para las diversas estatinas en base al fenotipo, predicho previamente por el análisis del genotipo. Los datos se basan en la guía del CPIC [ 9 ] y los metaanálisis [ 45 , 46 , 48 ]. Es aconsejable realizar el análisis del genotipo antes de iniciar el tratamiento y así poder considerar las recomendaciones pertinentes respecto al tipo y dosis de estatina.…”
Section: Farmacogenéticaunclassified
“…For instance, a clinical trial [ 14 ] revealed that the rs2231142 variant significantly improved the pharmacokinetics of fluvastatin and simvastatin. In contrast, a systematic review with meta-analysis [ 15 ] showed that the rs2231142 variant significantly increased the pharmacokinetics of rosuvastatin. In addition, a systematic review without meta-analysis [ 16 ] reported that the impact of rs2231142 on statin pharmacokinetics was stronger in rosuvastatin than in fluvastatin and simvastatin.…”
Section: Introductionmentioning
confidence: 99%